Does inheritance taxation stimulate or hamper human capital accumulation? - Dudek, Maciej; Kruszewski, Robert; Kudła, Janusz; Walczyk, Konrad (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: The taxes imposed on inheritance can stimulate or hamper accumulation of human capital, but it is unclear which of these prevails. Methodology: The study analysed the problem in the long run with the dynastic model using two approaches. In the first, human capital was approximated by wages, whilst in the second it constituted a separate production factor. The former refers to the complementarity between two types of capital, while the latter refers to the substitutability. Results: If wages approximate human capital, the inheritance tax decreases human capital accumulation. If, however, it is a distinct production factor, then the tax does not affect the accumulation rate but positively impacts the ratio of human to physical capital. Implications and recommendations: Inheritance taxation can stimulate labour-intensive and environmentally friendly production without harming economic growth if human and physical capital are the substitutes. Future research should involve the empirical verification of postulated results. Originality/value: The authors explained theoretically why inheritance taxation sometimes hampers and sometimes stimulates human capital accumulation without referring to different capital accumulation models, but only to the complementarity or substitutability of various types of capital.
Argumenta Oeconomica, 2025, Nr 2 (55), s. 204-217
Keywords: human capital; capital accumulation; bequest taxation; economic growth; inheritance